Relationship between Good Organizational Governance and the Performance Improvement of the Employees at Tax Affairs Organization in Ardebil Province - Behzad Jeloudarlu; Shahram Begzadeh (International Journal of Management, Accounting and Economics, 2016)
Regarding the purpose, the present study is an applied research and descriptive - correlational in terms of procedure and aims to investigate the relationship between good organizational governance and the performance improvement of the employees at Tax Affairs Organization in Ardebil province. Desk study and a questionnaire were used for data collection. The data collection tools in this study were standardized questionnaires, the validity and reliability of which were confirmed. The statistical population of this study included all male and female employees in Tax Affairs Organization in Ardebil province who were 320 individuals and the simple random sampling method was used to distribute the questionnaires. To investigate the hypothesis and analyze the data, the descriptive and inferential statistics were used in SPSS software. The Kolmogorov-Smirnov test results with the significance level of P>0.05 indicated the normal statistical distribution of the good organizational governance. Based on these findings, the Spearman correlation coefficient was used to examine the hypotheses. The results indicated that there is a significant relationship between the good organizational governance and its dimensions with the performance improvement of the employees in Tax Affairs Organization in Ardabil province.